The contribution of physical and sports activities in activating the values of citizenship among the students of the Department of Media and Sports Communication (Second year bachelor’s degree model - University of M’sila ) - betat noureddine (sports creativity, 2025)
The present study aimed at exploring the contributions of physical and sports activities in activating and consolidating the values of citizenship among the students of the Department of Media and Sports Communication univ-msila. The descriptive approach was used. :The study resulted in the following resultsThe study sample consisted of 34 students. 1-Physical and sports activities contribute to the development of the spirit of belonging to the homeland among the members of the research sample. 2-Physical and sports activities contribute to the modification of the behavior of the members of the research sample. 3-Physical and sports activities contribute to the development of community participation among the members of the research sample.